Influence of digital banking channels on the number of branches in European Union countries and Serbia - Putica, Maja (Anali Ekonomskog fakulteta u Subotici, 2020)
This study analyses the use of digital banking channels in the European Union and Serbia and the effect of their use on the number of branches. The aim of the study is to identify the banking channels, which explain the differences between these countries and to examine the existence of digital channels effect on the variation in the number of branches. The paper applied several statistical methods of multivariate analysis. Using factor analysis, the main factors were identified in the light of clarifying differences between countries, and the multiple linear regression method examined the influence of two independent variables-digital channels, representative for identified factors, on the dependent variable-number of branches. The research results show that there are significant differences between the examined countries in terms of credit card and direct debit services use. Variable that has a significant effect on reducing the number of branches is direct debit services usage.